2017
DOI: 10.1016/j.jchf.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Soluble Suppression of Tumorigenicity-2 and Prognosis in Acute Heart Failure

Abstract: OBJECTIVES The aim of this study was to perform a meta-analysis of currently available data regarding the prognostic significance of soluble suppression of tumorigenecity-2 (sST2) concentration in acute heart failure (AHF).BACKGROUND Concentration of sST2 may have prognostic value in AHF. A comprehensive assessment of all available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 37 publications
(20 reference statements)
2
103
0
7
Order By: Relevance
“…sST2 is a promising new biomarker in risk stratification and therapy guidance [69,70] in patients with acute and chronic heart failure, and was associated with an increased risk of adverse outcomes in previous trials [12,71,72]. According to our present findings, sST2 might be a useful additional biomarker in the management of patients with CVD and concomitant CKD, with or without albuminuria.…”
Section: Discussionsupporting
confidence: 72%
“…sST2 is a promising new biomarker in risk stratification and therapy guidance [69,70] in patients with acute and chronic heart failure, and was associated with an increased risk of adverse outcomes in previous trials [12,71,72]. According to our present findings, sST2 might be a useful additional biomarker in the management of patients with CVD and concomitant CKD, with or without albuminuria.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, sST2 was not associated with LV structure or LV systolic or diastolic function (AbouEzzeddine et al, 2017). Thus, these findings confirmed that the sST2 is rather a systemic inflammatory marker of extra cardiac origin of HF deteriorations than a single prognosticator of HF evolution, while meta-analysis provided by Aimo et al (2017) (Aimo et al, 2017) pointed that sST2 level may predict all-cause and CV death in HF patients at admission and at discharge from the hospital. Overall, there is a large body of evidence regarding that improved discriminative value of multiple biomarkers in HF patients requires much more accurate confirmation Pouleur, 2015).…”
Section: Limitations In Use Of Conventional Biomarkers In Hfmentioning
confidence: 59%
“…Our group [35] validated for the first time, the predictive value of sST2 in atrial fibrillation (AF) patients and concluded that sST2 levels had independent predictive value for all-cause mortality. Indeed, several groups have demonstrated the role of sST2 in cardiovascular events [36,37]. The recent clinical guidelines have recommended the use of biomarkers to further refine stroke and bleeding risk in AF patients [38].…”
Section: Detection Of Central Venous Catheter-related Bloodstream Infmentioning
confidence: 99%